Comparative study of healing of fracture of metacarpus in calves using different external immobilisation methods - Kalyani Biswas (Department of Surgery, College of Veterinary and Animal Science, 1990)
The study was conducted on 18 crossbred male calves divided in three groups of six animals each. Under local anaesthesia (ring block) fracture was created at the midshaft region of the large metacarpal and was reduced. The limb was immobilized with (i) plaster of paris cast (Group A), (ii) transfixation apparatus and plaster of paris cast (group B) and (iii) cast using freshly prepared gum and bandgage (group C).